"I found it very special and interesting": Evaluative language in Master's thesis defenses in Taiwan universities. Issue 53 (September 2021) - Lin, Chia-Yen; Lau, Ken
Abstract: Evaluation has been identified as a significant feature of both written and spoken academic discourse. However, few studies have discussed how evaluative language is used to construct meaning in oral defenses, and even less is known about the topic in oral defenses conducted in English as a lingua franca contexts. To fill this research gap, the present study draws on Martin and White's (2005) appraisal theory to quantitatively and qualitatively examine evaluative language in a corpus of English-medium Master's thesis defenses carried out in Taiwan universities. The results show that the three attitudinal resources were used to surprisingly similar extent, which suggests that the theses and oral presentations preceding the Q&A sessions are objectively appreciated, that the examiners are emotionally affected, and that the candidates' abilities, particularly their research capacity, are being judged. This phenomenon can be attributed to the common academic discourse convention of objectifying the subjective practice of the evaluating entity and the physical presence of the participants. Examiners draw on expressions of subjective feelings to personalize their evaluative discourse, which contributes to the creation of interpersonal relationships during these high-stakes assessment events. This effect is enhanced by the use of evoked attitude type and graduation.